Evaluasi Performa Alat Uji Bending Sederhana untuk Pengujian Sambungan Las Baja Karbon Rendah - Ike Anggraini Subono; Aulya Putri Wardani; Ipung Kurniawan; Ulikaryani Ulikaryani; Joko Setia Pribadi; Dian Prabowo; Pujono (Infotekmesin, 2026)
Bending testing is a method used to evaluate the quality of welded joints; however, the limited availability of Universal Testing Machines (UTMs) can hinder testing and educational activities. This study aims to evaluate the performance of a simple bending test apparatus based on its ability to generate loading data, measurement result consistency, responsiveness to welding parameter variations, and preliminary alignment with data from previous studies. The tests utilized low-carbon steel specimens (6 mm thick) welded via the SMAW method using 3.2 mm diameter E7016 electrodes at current settings of 110 A and 120 A. Testing employed face-bending and root-bending configurations, with four specimens tested for each. Maximum loads were recorded using a load cell integrated with an HX711 module and Arduino, and subsequently used to calculate bending stress. Analysis was based on mean values, standard deviation, the coefficient of variation (CV), and visual inspection for cracks in the Heat-Affected Zone (HAZ). Results indicated bending stresses ranging from 553.8 to 794.7 MPa. Mean face-bending stress increased from 599.70 MPa at 110 A to 729.45 MPa at 120 A, while mean root-bending stress rose from 632.73 MPa to 740.63 MPa. CV values ranged from 2.45% to 10.86%. Comparisons with previous research revealed deviations of 50.17% at 110 A and 43.72% at 120 A. The findings demonstrate that the apparatus is capable of generating quantitative data and capturing changes in bending response; however, direct validation against a standard UTM is still required to determine measurement accuracy.